Can Vitamin D Mitigate Osteoarthritic Hip Joint Arthroplasty Infections Among Older Adults? A Narrative Overview of the Literature Amidst COVID-19 Lockdowns and Beyond - Marks, Ray (Journal of Aging Research And Healthcare, 2021)
Background Older adults with hip joint osteoarthritis, a major cause of chronic progressively disabling highly painful functional experiences, may require a surgical joint replacement procedure known as total joint arthroplasty surgery. Objective This review aimed to address the question of whether there an association between hip joint arthroplasty infection rates and prevailing pre or preoperative vitamin D levels that warrants consideration in efforts to prevent or minimize infection related hip arthroplasty complications among older adults particularly during the current ongoing COVID-19 pandemic. Methods PUBMED, SCOPUS, and WEB OF SCIENCE articles related to the topic and published between January 2016-2021 were searched, examined, and summarized. Results Older adults with hip joint osteoarthritis and low vitamin D serum levels who undergo total hip joint arthroplasty surgery may be at higher risk for post-operative infections than those with adequate vitamin D serum levels. Conclusion More research to verify whether efforts to screen for, and maximize vitamin D levels, before and after surgery, as indicated, may be helpful in the context of minimizing total hip joint arthroplasty surgery infection susceptibility and severity among older vitamin D deficient severely disabled hip osteoarthritis cases.
Keywords: Vitamin D; Hip Joint Arthroplasty; Hip Osteoarthritis; Joint Infection; COVID-19; Older Adults; Hypovitaminosis D